Powieść afrykańska - Coetzee, John Maxwell (Er(r)go. Teoria - Literatura - Kultura, 2004)
J . M. Coetzee The Novel in Africa In Coetzee' s story, Elizabeth Costello, an Australian writer, boards an ocean-liner to entertain its passengers by giving talks about literature. Her fellow-entertainer is Emmanuel Egudu, a Nigerian writer lecturing on "The Novel in Africa". In his talk Egudu emphasises his Africanness, a special African identity. In conversation, the two characters discuss the novel in Africa; Elizabeth opines that what distinguishes the African novel is that it is not written for Africans but for foreigners. That fact imposes both restrictions and obligations on the African writer, which Coetee' s story illustrates and explores. What it also exposes is the naivety involved in drawing precipitous conclusions and offering generalisations based on a person's language, profession and ethnic origins.